2022
DOI: 10.33308/26674874.2022361354
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Eğitim ve Öğretim Programları, Çevre Okuryazarlığının Gerçekleştirilmesini Ne Kadar Desteklemektedir?

Abstract: Çevre eğitiminin amacı, toplumdaki bireyleri çevre sorunları konusunda aktif katılım gösteren çevre okuryazarı bireyler yapmaktır. Eğitim ve öğretim programları da öğrencilerin çevre okuryazarlığı kazanmalarını amaçlamaktadır. Çalışmanın amacı, okul öncesinden liseye eğitim ve öğretim programlarının kazanımlarının, çevre eğitimi amaçlarının kazandırılmasını ne kadar desteklediğini belirlemektir. İncelenen programlar, çevre eğitimi amaçlarının alt unsurları olan bilinç, bilgi, tutum, beceri, katılım kategoriler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…We studied general youth in Turkey who are inactive in climate activism and movements. Recently Turkey introduced an elective course on 'environmental education and climate change' (MEB, 2022), but before that, environmental topics were taught through other courses like life science, science and biology (Öz-Aydın et al, 2022). Many high school students in Turkey find opportunities to participate in TUBITAK-funded (research institute in Turkey) projects on climate change with teacher supervision.…”
Section: Introductionmentioning
confidence: 99%
“…We studied general youth in Turkey who are inactive in climate activism and movements. Recently Turkey introduced an elective course on 'environmental education and climate change' (MEB, 2022), but before that, environmental topics were taught through other courses like life science, science and biology (Öz-Aydın et al, 2022). Many high school students in Turkey find opportunities to participate in TUBITAK-funded (research institute in Turkey) projects on climate change with teacher supervision.…”
Section: Introductionmentioning
confidence: 99%
“…When reviewing the environmental education literature, it was found that the subject was approached from various perspectives. Some of these studies (Adıyaman, 2021;Akınoğlu & Sarı, 2009;Aktaş, 2019;Alım, 2006;Demirezen & Kaya, 2022;Demirkaya, 2006;Dere & Çinikaya, 2023;Gülersoy et al 2020;Güngör-Cabbar et al 2020;Koto, 2020;Gürkan, 2019;Demir & Yalçın, 2014;Güven & Hamalosmanoğlu, 2012;Muşlu-Kaygısız, 2020;Öz-Aydın et al 2022;Şahin, 2021;Tanrıverdi, 2009;Turan & Koç, 2021;Yılmaz, 2016;Yolcu, 2014) analyzed various programs at the primary education (primary school + secondary school) level. In addition, several studies (Demirkaya, 2006;Demir & Yalçın, 2014;Erdoğan et al, 2012;Gülersoy et al, 2020;Uzun & Sağlam, 2007;Ünal & Dımışkı, 1999) investigated the state of environmental education in the secondary education curriculum.…”
Section: Introductionmentioning
confidence: 99%